TEACHERS AS FACILITATORS IN OVERCOMING BARRIERS TO ARABIC SPEAKING SKILLS THROUGH AN IMMERSION-BASED APPROACH AT MA ASSALAM BOARDING SCHOOL - Dinda Pramesti Agista Cahyani; Amin Nasir; Habib Maulana Maslahul Adi (Al Ibrah: Journal of Arabic Language Education, 2026)
This study analyzes the strategic role of teachers as facilitators in overcoming barriers to learning Arabic speaking skills at MA Assalam Tuban, an Islamic boarding school adopting the Gontor model. A qualitative case study design is used with data collected through in-depth interviews, participant observation, and documentation, followed by thematic analysis using data reduction, data display, and conclusion drawing. The findings show that teachers act as designers of a communicative and immersive environment by applying the direct/ummah method and organizing structured speaking activities such as muhadasah, khitobah, drama, and intensive language programs. Linguistic and non-linguistic barriers are addressed through religiously grounded motivation, a comprehensive oral (syafahi) assessment system, and a pesantren culture that normalizes mistakes, enabling first-year students to reach functional fluency within about six months.